Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia - Shanty Y. Rachmat; Ganesha G. Mangkoesoebroto (Journal of Infrastructure & Facility Asset Management, 2022)
The COVID-19 outbreak cuts the number of trips and people’s movement during the day. Not only because of the community’s awareness for the disease transmission but also because of the enforcement from the government to apply the mobility policy. This changing trip behavior is predicted to happen throughout the time of pandemic and post-pandemic. On the contrary, when mobility is decreasing, the role of ICT in community activities is increasing. This condition leads to an interesting question for the smart city, especially the smart mobility concept, whether the smart mobility concept has been properly addressed and responded to the pandemic and post-pandemic era or not. This paper aims to explore how far smart mobility planning has been applied by local governments in Indonesia, especially in response to community activity during the pandemic era. Our approach in this paper is a qualitative study in evaluating online local government planning documents as our main data. We choose the study cases in three cities that got high tier ranks in the smart city awards in 2019 (based on Rating Kota Cerdas Indonesia/Indonesia’s Smart Cities Rating), which are Semarang, Samarinda, Magelang. We review literature on smart mobility indicators and those smart mobility indicators used in planning documents. Then, we evaluate the relevance of those indicators to the condition of pandemic and post pandemic era. We found that smart mobility indicators have not been received much concern as the main aspect of smart city in Indonesia.